IMPLEMENTATION OF TEACHER STRATEGIES IN RAISING ANTI-BULLYING AWARENESS OF FOURTH GRADE STUDENTS AT MUHAMMADIYAH PLUS ELEMENTARY SCHOOL SEMARANG - Sari, Tiara Kartika; Asih, Sri Sami (STKIP Citra Bakti, 2026)
This study is motivated by the prevalence of bullying within elementary school social circles, specifically targeting physical differences such as height, weight, and skin color, as well as verbal abuse involving the disrespectful use of parents' names. These behaviors are driven by school and residential environments, alongside the rapid influence of technology on student conduct. This research aims to analyze the implementation of teacher strategies in fostering anti bullying awareness through the memorization of short quranic surahs and daily prayers. Using a qualitative descriptive method with data triangulation comprising semi structured and in depth interviews, classroom observations, and documentation the study involved a fourth grade teacher and four students as participants. The findings indicate that integrating short surah memorization and daily prayers effectively raises awareness and mitigates bullying among fourth graders by providing spiritual understanding and emotional tranquility, which encourages patience and tolerance. Consequently, the study concludes that implementing these religious character building strategies successfully addresses bullying issues, offering an empirical foundation for character education as a solution to social problems in faith-based elementary schools.